Acute post-streptococcal glomerulonephritis – immune-mediated acute kidney injury – case report and literature review - Piotr Skrzypczyk; Anna Ofiara; Anna Zacharzewska; Małgorzata Pańczyk-Tomaszewska (Central European Journal of Immunology)
Acute post-streptococcal glomerulonephritis (APSGN) is an immunological complication of infection with group A -hemolytic streptococcus (GAS). The disease manifests as microscopic or gross hematuria, arterial hypertension, edema, and acute kidney injury and has most commonly a self-limiting course. We report a very severe case of APSGN in a 5-year-old girl with superimposed generalized infection. The girl presented significant overhydration, a very low glomerular filtration rate (GFR) (11.2 ml/min/1.73 m 2 ), hyperuricemia (12.7 mg/dl), nephrotic proteinuria, and gross hematuria. Her immunological tests allowed for the diagnosis of APSGN (elevated antistreptolysin O [ASO] titer, low C3, and normal C4 complement factors). She also showed very high inflammatory indicators suggestive of sepsis. She received supportive treatment together with ceftriaxone and a single dose of rasburicase. Her renal function recovered, and urinalysis normalized. Gallbladder deposits complicated the treatment. This article summarizes the existing knowledge on APSGN with particular emphasis on the immunological mechanisms of the disease. The proposed immunological pathway leading to glomerular injury is discussed. In children, APSGN has an excellent prognosis, including in cases with severe renal impairment in the early stages of the disease.